Fungsi Sekretariat Dewan Perwakilan Rakyat Daerah (DPRD) Deli Serdang - Maulana, Syahlaa (Universitas Labuhanbatu, 2023)
The DPRD Secretariat is an element of administrative services and provides support for the DPRD's duties and functions. The DPRD Secretariat is led by the DPRD Secretary whose operational position is technically subordinate to and responsible to the DPRD Leadership and administratively responsible to the Regent through the Regional Secretary. The DPRD Secretariat has the task of carrying out secretarial and financial administration, supporting the implementation of the DPRD's duties and functions, as well as providing and coordinating the expert staff needed by the DPRD to carry out its rights and functions according to needs. The DPRD Secretariat, in carrying out its main tasks, carries out the following functions: Carrying out DPRD secretariat administration, Carrying out DPRD financial administration, Facilitating the holding of DPRD meetings, and Providing and coordinating expert staff required by the DPRD.